PENULISAN BERITA CITIZEN JOURNALISM PADA RUBRIK CITIZEN REPORT DI HARIAN TRIBUN PEKANBARU - Bynton Simanungkalit; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Citizen Journalism phenomenon began to spread to the people of Riau. Tribun Pekanbaru as local media into a battering ram that provide space for people to write down related to the problems they face, named Rubric Citizen Report. This rubric contained 32 pages and is published every Monday through Saturday. Through the rubric of free citizens to write about all the problems they face, but there are still many shortcomings during the writing rubric news in the Citizen Report. Therefore, this study aims to determine the process of citizen journalism in news writing rubric Citizen Report on Tribun Pekanbaru daily and know the elements of citizen journalism on the news section on the Citizen Report Tribun Pekanbaru contained in the writings of the residents.This study uses descriptive qualitative in-depth interviews. This study also used a model of agenda setting that emphasizes Tribun Pekanbaru provides a rubric Citizen Report with a view to involving the community as a supervisor in any problems that occur. This study was carried out on the rubric Citizen Report published 22 November until 19 June 2014 subject of this study is divided into two groups, namely from the Tribun editorial Pekanbaru comprising Chief Editor, senior editor, editor in charge of Pages, and that settle Reporter posts. Both come from the writing rubric citizen Citizen Report.The result of this study is the first no determination of topics, both rely on the fact that something will be seen, the third never do interviews, four editing process is done ignoring the rules in news writing, comprehension five residents will be writing the news still is lacking. Meanwhile, news of the elements found some results of research that has been done, the first article of citizens still included in the actual category, two posts citizens still show a number of facts, three residents and editors still consider the importance of a phenomenon to be used as news, the fourth events that made news by residents are still included in the category of interest.Keywords: News writing, citizen journalism and news element.